INHIBITORY PROCESSES FROM THE CEREBRAL CORTEX - OBRADOR ALCALDE, S (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1945)
Review of results of frontal lobectomy The authors conclude that the frontal lobe is a double structure, with overlapping opposing functions, which must be investigated by more precisely limited exptl lesions
CIENC MEX
Keywords: INHIBITORY, PROCESSES, CEREBRAL, CORTEX; CIENCIAS MEDICAS; MEDICINA INTERNA; NEUROLOGIA